(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: Caroli’s disease; cholangitis; oesophageal varices; ductal stone; ductal plate; ductal plate malformation central dot sign; common bile duct doi: 10.3329/jcmcta.v19i1.3853 Journal of Chittagong Medical College Teachers’ Association 2008: 19(1):46-49